(2,9-Dimethyl-1,10-phenanthroline-κ(2) N,N′)bis(2-methoxybenzoato-κ(2) O (1),O (1′))cadmium - Zhang, Heng (International Union of Crystallography, 2012)
In the title compound, [Cd(C(8)H(7)O(3))(2)(C(14)H(12)N(2))], the Cd(II) ion is coordinated by two N atoms from a 2,9-dimethyl-1,10-phenanthroline (dmphen) ligand and four O atoms from two 2-methoxybenzoate anions in a distorted octahedral environment. Two O atoms of one bidentate 2-methoxybenzoate ligand are each disordered over two positions, with site-occupancy factors of 0.579 (4) and 0.421 (4). In the crystal, molecules are linked by C—H⋯O hydrogen bonds, forming a two-dimensional network lieing parallel to the bc plane. The crystal packing is further stablized by π–π stacking interactions between the dmphen rings of neighboring molecules, with distances between their parallel dmphen ring planes of 3.517 (3) and 3.610 (3) Å.